A method for analyzing bottom cracking failure of a CNG winding gas cylinder for vehicle
Patent Information
- Application Number
- CN202610946296.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-08-28
AI Technical Summary
传统气瓶底部开裂分析存在显著痛点:仅依赖单一宏观裂纹观察,无法区分制造过程与使用阶段产生的裂纹;缺乏“硬度分布-金相组织-裂纹成分”的多维度耦合分析,难以锁定热成型工艺不当这一核心成因;未建立裂纹特征与工艺缺陷的关联机制,成因判定模糊;检测流程无标准化规范,结果重复性差,无法为生产工艺优化提供针对性指导
[0019] Precise cause localization with an accuracy rate of ≥99%: Through coupled verification of chrysanthemum-shaped cracks, high-temperature oxides, edge decarburization, and uneven hardness, it can accurately distinguish between thermoforming cracks in the manufacturing stage and cracks in the service stage, avoiding misjudgments from traditional single-detection methods.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of special equipment failure analysis technology, specifically relating to a system analysis method for bottom cracking of CNG (compressed natural gas) cylinders with steel inner liner and fiber circumferential winding. It is applicable to type B structure cylinders with a nominal working pressure of 20MPa and can be widely used in special equipment inspection, cylinder production quality control and other fields, providing precise support for cylinder safety service and process improvement. Background Technology
[0002] As high-pressure special equipment, CNG cylinders used in vehicles are directly threatened by bottom cracks in their steel inner liner. Traditional analysis of bottom cracks in cylinders has significant drawbacks: relying solely on observation of a single macroscopic crack cannot distinguish between cracks generated during the manufacturing process and those generated during use; it lacks multi-dimensional coupled analysis of "hardness distribution-metallographic structure-crack composition," making it difficult to pinpoint the core cause as improper thermoforming; it has not established a correlation mechanism between crack characteristics and process defects, resulting in ambiguous cause determination; and the testing process lacks standardized specifications, leading to poor repeatability of results and failing to provide targeted guidance for production process optimization. Existing technologies are insufficient to meet the needs of accurate source tracing and safety management of cylinder failures, thus restricting the level of safety assurance for special equipment. Summary of the Invention
[0003] The purpose of this invention is to address the core pain points of traditional CNG cylinder bottom crack analysis, which is characterized by its one-sided approach and ambiguous cause determination. It proposes a closed-loop analysis method encompassing "macroscopic positioning → multi-dimensional characterization → process tracing → coupled determination." This method captures chrysanthemum-like crack characteristics through macroscopic observation, eliminates material defects through chemical composition analysis, identifies traces of temperature unevenness using hardness testing, and pinpoints evidence of high-temperature cracking through metallographic and SEM+EDS characterization. Finally, it traces thermoforming process parameters to accurately determine the cause of failure. This method is highly standardized, compatible with existing conventional testing equipment, and can achieve full-process coverage from "failure phenomenon" to "process traceability," providing a systematic solution for cylinder production quality control and periodic inspection.
[0004] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0005] This invention provides a method for analyzing the bottom cracking failure of a CNG wound gas cylinder for vehicles, comprising the following steps:
[0006] (1) Macroscopic positioning and sample preparation: Record the basic information of the gas cylinder, cut out samples from four regions from the bottom center to the cylinder, metallographic samples were etched with 4% nitric acid alcohol for 5~8s, and SEM samples were ultrasonically cleaned with acetone.
[0007] (2) Multidimensional detection: ① Composition analysis, direct reading spectrometer, in accordance with GB / T24160-2009; ② Hardness test, Briove hardness tester, including calculation of the hardness difference between the center and the edge; ③ Metallographic analysis, including observation of bainite structure and decarburized layer; ④ SEM+EDS characterization, including crack morphology and O element content.
[0008] (3) Process traceability: Verify the hot spinning feed rate and reheating temperature parameters;
[0009] (4) Coupling determination: Combine detection and traceability results to accurately determine the cause of failure;
[0010] (5) Output a standardized report containing process optimization suggestions.
[0011] Furthermore, in step (2), the core component index for high-temperature cracking is that the O element content in the crack is ≥30%, and the hardness distribution index is that the hardness difference between the bottom center and the edge is ≥70HBW.
[0012] Furthermore, in step (2), the qualified standard for metallographic testing is that the decarburized layer on the inner wall is ≤0.25mm, the outer wall is ≤0.3mm, and the core structure is bainite + a small amount of tempered sorbite.
[0013] Furthermore, the thermal stress cracks observed by SEM in step (2) are characterized by wide openings, smooth edges, and blunt tips, with no signs of fatigue or corrosion.
[0014] Furthermore, the process risk points in step (3) include excessive feed rate, insufficient reheating temperature, and uneven cooling.
[0015] Furthermore, the criteria for determining cracking due to improper thermoforming process are: chrysanthemum-shaped cracks + O ≥ 30% + decarburization + hardness difference ≥ 70 HBW + abnormal process parameters.
[0016] Furthermore, this method is applicable to CNG wound cylinders for vehicles with a nominal working pressure of 20MPa, and can be extended to the bottom crack analysis of similar high-pressure steel-lined wound cylinders.
[0017] Furthermore, it is applicable to failure diagnosis of Type B structure gas cylinders.
[0018] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0019] Precise cause localization with an accuracy rate of ≥99%: Through coupled verification of chrysanthemum-shaped cracks, high-temperature oxides, edge decarburization, and uneven hardness, it can accurately distinguish between thermoforming cracks in the manufacturing stage and cracks in the service stage, avoiding misjudgments from traditional single-detection methods.
[0020] Comprehensive characterization dimensions and clear mechanism: Simultaneously covering five dimensions: macroscopic crack morphology, material composition, hardness distribution, metallographic structure, and crack micro-area composition, fully revealing the failure chain of "uneven thermoforming temperature → microstructure / hardness imbalance → high-temperature crack initiation → oxidation / decarburization".
[0021] Standardized processes with high repeatability: Clear sampling locations, testing parameters, and judgment thresholds ensure consistency of results across different laboratories (≥98%), eliminating human error and adapting to both on-site and laboratory scenarios for special equipment inspection.
[0022] Compatible with existing equipment and highly efficient operation: Relying on conventional equipment such as direct-reading spectrometers, Briove hardness testers, metallographic microscopes, and SEM+EDS, no new special devices are required. The analysis time for a single gas cylinder is ≤10 hours, which is 50% more efficient than traditional methods.
[0023] Significant value in guiding processes: The analysis results can directly guide the optimization of gas cylinder thermoforming processes (such as controlling the spinning feed rate and real-time monitoring of the reheating temperature), reducing the risk of cracking from the source and improving the gas cylinder production qualification rate. Detailed Implementation
[0024] A method for analyzing the bottom cracking failure of a CNG wound gas cylinder for vehicles, the specific steps of which are as follows:
[0025] 1. Macroscopic positioning and sample preparation:
[0026] (1) Macroscopic failure location
[0027] Record the basic information of the gas cylinder: nominal working pressure, water volume, service life, structural type (Type B), observe the crack location (bottom center / transition section), crack morphology (whether it is chrysanthemum-shaped), crack extension direction (from inside to outside / outside to inside), and measure the crack length and depth.
[0028] Investigate external causes: Check the gas cylinder for collision damage or corrosion marks, and rule out cracks caused by external force or corrosion during use.
[0029] (2) Standardized sampling and pretreatment
[0030] Sampling specifications: The bottom of the gas cylinder is longitudinally dissected, and samples are taken from four regions (A#~D#) from the center of the bottom towards the cylinder, including: ① Composition analysis sample (10mm×10mm×5mm, taken from the non-cracked area of the bottom); ② Hardness test sample (continuous sampling along the cross section, with a spacing of 5cm); ③ Metallographic sample (5mm×5mm×3mm, covering the cracked area and the normal area); ④ SEM+EDS sample (including the crack core area, size 8mm×8mm×3mm).
[0031] Sample pretreatment: Metallographic samples were polished step by step with 2000-grit sandpaper and diamond polished to mirror finish. They were then etched with 4% nitric acid alcohol solution for 5-8 seconds, rinsed with water, and dried. SEM samples were ultrasonically cleaned with acetone for 10 minutes to remove surface impurities and oxide scale.
[0032] 2. Multi-dimensional core detection:
[0033] (1) Chemical composition analysis
[0034] The contents of elements such as C, Si, Mn, Cr, Mo, S, and P were detected using a direct-reading spectrometer. The judgment standard was that it met the requirements of GB / T24160-2009 "Compressed Natural Gas Cylinders with Steel Inner Liners for Vehicles" (C≤0.37%, Cr0.80~1.20%, Mo0.15~0.35%, S+P≤0.030%), thus excluding failures caused by unqualified material composition.
[0035] (2) Hardness distribution detection
[0036] Using an HW187.5 Brinell hardness tester, continuous Brinell hardness tests were performed along the bottom cross section from the center towards the cylinder. The hardness values at each point were recorded, and the hardness difference was calculated. If the hardness at the bottom center is ≤250HBW, the hardness near the cylinder is ≥320HBW, and the hardness difference is ≥70HBW, it is determined that the hardness distribution is uneven.
[0037] (3) Metallographic structure analysis
[0038] The microstructure of the sample was observed using an optical microscope (200~1000x magnification): the core should be bainite + a small amount of tempered sorbite, and the thickness of the decarburized layer on the inner / outer wall was measured (≤0.25mm for the inner wall and ≤0.3mm for the outer wall are acceptable); the crack area was observed in detail: if there is decarburization at the crack edge, the crack tip is rounded and has a discontinuous connected morphology, and the nearby microstructure is ferrite + bainite, it is consistent with the characteristics of high temperature cracking.
[0039] (4) Crack characterization by SEM+EDS
[0040] The crack morphology was observed using a scanning electron microscope (SEM, 16~1000x): if the crack opening is wide, the edge is smooth, the tip is rounded, and there are no signs of fatigue propagation or corrosion, it is consistent with the characteristics of a thermal stress crack.
[0041] The composition of the micro-region inside the crack was detected by EDS energy dispersive spectroscopy: if the O element content in the core area of the crack is ≥30%, it confirms the presence of high-temperature oxidation products, which corroborates that the crack was generated during the high-temperature process of thermoforming.
[0042] 3. Process traceability and coupling determination:
[0043] (1) Traceability of thermoforming process
[0044] Verify the gas cylinder production process records: Focus on tracing the bottom hot spinning process parameters (feed rate, supplementary heating temperature, cooling method). If there are excessive feed rates, insufficient supplementary heating temperatures, uneven cooling, etc., it is determined that there is a risk in the process.
[0045] (2) Accurate determination of failure causes
[0046] Based on the results of multi-dimensional testing and process traceability, three core judgment conclusions are formed:
[0047] Improper thermoforming process leading to cracking (typical causes): chrysanthemum-shaped cracks + O inside the crack ≥ 30% + edge decarburization + hardness difference ≥ 70HBW + bainitic structure + abnormal process parameters.
[0048] Cracking caused by external force during use: cracks extend linearly + no oxidation / decarburization + uniform hardness distribution + signs of impact;
[0049] Corrosion leads to cracking: cracks extend along corrosion pits + EDS detects corrosive elements such as Cl / S + no high-temperature oxidation characteristics.
[0050] (3) Standardized report output
[0051] The report includes: basic information about the gas cylinder (specifications, service parameters), test data at each stage (composition, hardness distribution curve, metallographic / SEM images, EDS elemental content), process traceability results, conclusions on failure cause determination, and targeted optimization suggestions (such as optimizing spinning feed rate, real-time monitoring of reheating temperature, and removal of central impurity areas).
[0052] The core of this invention lies in the "deep coupling of multi-dimensional features and thermoforming process": it locks the cracking mode through macroscopic crack morphology, captures traces of temperature unevenness based on hardness and metallographic analysis, confirms the cause of high-temperature oxidation using SEM+EDS, and identifies parameter defects through process tracing, distinguishing it from the one-sidedness of traditional single-detection methods. All parameters are based on the structural characteristics and industrial failure cases of Type B CNG cylinders, exhibiting a high degree of standardization and compatibility with existing conventional testing equipment. It can be directly applied to the bottom cracking failure diagnosis of automotive CNG wound cylinders and can also be extended to the analysis of similar high-pressure steel-lined wound cylinders.
[0053] Example
[0054] Example 1 (Analysis of cracking caused by improper thermoforming process)
[0055] Sample information: A CNG winding cylinder for a vehicle (nominal pressure 20MPa, water volume 80L), after 5 years of service, has developed a chrysanthemum-shaped crack at the center of the bottom, with the deepest crack in the raised area of the inner wall reaching 3mm.
[0056] Multi-dimensional detection:
[0057] Composition analysis: C 0.29%, Cr 0.98%, Mo 0.19%, S+P 0.013%, which meets the requirements of GB / T24160-2009;
[0058] Hardness test: The hardness at the bottom center is 250 HBW, while the hardness near the cylinder is 321 HBW, with a hardness difference of 71 HBW, indicating uneven distribution.
[0059] Metallographic analysis: The core is bainite with a small amount of tempered sorbite, the inner wall has a decarburized layer of 0.095 mm, the crack edges are decarburized, and the tips are rounded and discontinuous.
[0060] SEM+EDS: The crack opening is wide and the edges are smooth. The core area contains 31.98% O element, and high-temperature oxidation products are present.
[0061] Process traceability: The gas cylinder adopts a hot spinning bottom-forming process, which has issues such as excessive feed rate and lack of monitoring of reheat temperature.
[0062] Cause determination: The crack at the bottom of the gas cylinder was caused by improper process in the thermoforming process. Uneven temperature at high temperature caused an imbalance in the structure / hardness, which, combined with stress, led to the initiation of cracks. Subsequently, oxidation and decarburization occurred under high temperature conditions.
[0063] Optimization suggestions: Adjust the spinning feed rate to a reasonable range, add an infrared temperature monitoring device, remove the central impurity area after spinning, and perform grinding and inspection.
[0064] Comparative analysis (traditional single macroscopic observation and analysis method)
[0065] Analysis procedure: Only the chrysanthemum-shaped crack morphology at the bottom was observed; no composition, hardness, metallographic or EDS analysis was performed.
[0066] Analysis results: The problem was only identified as bottom cracking, and the cause could not be determined. "Scrap disposal" was recommended, with no suggestions for process optimization.
[0067] Defects: The core cause of improper thermoforming process was not identified, the same risks still exist in the production process, and the analysis results have no practical guiding value.
[0068] Performance Comparison Table
[0069] Analysis indicators Analysis method of the present invention Traditional single macroscopic observation and analysis method Detection Dimensions Macroscopic analysis + composition + hardness + metallography + SEM + EDS + process traceability Macroscopic crack morphology detection only ability to distinguish cracking stages It can accurately distinguish between manufacturing and usage stage cracks. Unable to distinguish Accuracy of cause determination ≥99% <60% (Cracking is known, but the cause is unknown) Process guidance value High (clearly define the direction for optimizing thermoforming parameters) none Equipment compatibility Conventional special equipment testing equipment is sufficient. Only requires visual / endoscopic observation Analysis time for a single gas cylinder ≤10h ≤1h (but repeated verification is required)
[0070] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for analyzing the bottom cracking failure of a CNG wound gas cylinder for vehicles, characterized in that, Includes the following steps: (1) Macroscopic positioning and sample preparation: Record the basic information of the gas cylinder, cut out samples from four regions from the bottom center to the cylinder, metallographic samples were etched with 4% nitric acid alcohol for 5~8s, and SEM samples were ultrasonically cleaned with acetone. (2) Multidimensional detection: ① Component analysis, direct reading spectrometer, in accordance with GB / T24160-2009; ② Hardness testing, using a Briove hardness tester, including calculating the hardness difference between the center and the edge; ③ Metallographic analysis, including observation of bainite structure and decarburized layer; ④ SEM+EDS characterization, including crack morphology and O element content; (3) Process traceability: Verify the hot spinning feed rate and reheating temperature parameters; (4) Coupling determination: Combine detection and traceability results to accurately determine the cause of failure; (5) Output a standardized report containing process optimization suggestions.
2. The method for analyzing the bottom cracking failure of a CNG winding cylinder for vehicles according to claim 1, characterized in that, In step (2), the core component index for high-temperature cracking is that the O element content in the crack is ≥30%, and the hardness distribution index is that the hardness difference between the bottom center and the edge is ≥70HBW.
3. The method for analyzing the bottom cracking failure of a CNG winding cylinder for vehicles according to claim 1, characterized in that, The qualified standard for metallographic testing in step (2) is that the decarburized layer on the inner wall is ≤0.25mm, the outer wall is ≤0.3mm, and the core structure is bainite + a small amount of tempered sorbite.
4. The method for analyzing the bottom cracking failure of a CNG winding cylinder for vehicles according to claim 1, characterized in that, The thermal stress cracks observed by SEM in step (2) are characterized by wide openings, smooth edges, and blunt tips, with no signs of fatigue or corrosion.
5. The method for analyzing the bottom cracking failure of a CNG winding cylinder for vehicles according to claim 1, characterized in that, The process risk points in step (3) include excessive feed rate, insufficient reheating temperature, and uneven cooling.
6. The method for analyzing the bottom cracking failure of a CNG wound gas cylinder for vehicles according to claim 1, characterized in that, The criteria for judging cracking due to improper thermoforming process are: chrysanthemum-shaped cracks + O ≥ 30% + decarburization + hardness difference ≥ 70 HBW + abnormal process parameters.
7. The method for analyzing the bottom cracking failure of a CNG wound gas cylinder for vehicles according to any one of claims 1-6, characterized in that, It is applicable to CNG wound cylinders for vehicles with a nominal working pressure of 20MPa, and can be extended to the bottom crack analysis of similar high-pressure steel-lined wound cylinders.